Klasifikasi Genom dan Hubungan Kekerabatan Tanaman Pisang (Musa spp.) di Kabupaten Rokan Hulu berdasarkan Karakter Morfologi - Zulfahmi Zulfahmi; Nurliana Nurliana; Rosmaina Rosmaina (Universitas Sebelas Maret, 2024)
Banana is a fruit crop cultivated by the community of rokan hulu from generation to generation. The knowledge comprehensive on the banana crop in Rokan Hulu Regency is unavailable and its information an important to conservation and breeding program in the future. This study aimed to determine the genome classification and the genetic relationship among banana cultivars (Musa spp.) at Rokan Hulu District. The morphological characterization was performed by following the International Plant Genetic Resource Institute (IPGRI) standard. This study has successfully identified sixteen local banana cultivars. Based on morphological character that sixteen banana cultivars can be grouped into three genomes, first group was AA/AAA genome that consisted of Lidi, Somanih, Sminyak, Lomakmanih, and Pinang banana cultivars, second group was AAB genome that consisted of Sawak, Kapas, Bunga, Barangan, Udang, Raja, Mantan, Nangka, and Kapal cultivars, and last group was ABB genome that consisted of Batu and Kepok banana cultivars. The morphology similarity among cultivars ranged from 0.49 to 0.98. The lowest value of morphology similarity was observed between Nangka and Udang cultivars, meanwhile, the highest value of morphology similarity was observed between Mantan and Somanih cultivars. Dendrogram UPGMA based on morphological similarity (68%) clustered all cultivars into four main groups. The first cluster consisted of Batu, Raja, Nangka, Barangan, and Kapas banana cultivars, The second group consisted of Sawak and Pinang banana cultivars. The third group consisted of Lomakmanih, Sminyak, Mantan, Lidi, Kapal, and Somanih banana cultivars, and the fourth group consisted of Bunga dan Udang banana cultivar. The clustering result did not reflected genome classification of banana cultivar. The results of this study could be used as the basic information to formulate the breeding and conservation strategies of banana in Rokan Hulu regency in the future.